KEABSAHAN PENGHADAP YANG MENGHADAP SECARA DARING DALAM CYBER-NOTARY - Limantara, Nagawati; Barkatullah, Abdul Halim; Zulaeha, Mulyani (Collegium Studiosum Journal, 2023)
Progress in the digital era has made technological advances increasingly sophisticated and rapid so that the use of various digital media is very necessary for society. The shift in activities that were previously carried out conventionally is slowly shifting to online or better known as "online", such as the use of applications zoom as an application for face to face. Activities in the notarial world are also experiencing the impact of changes in this era, which are known as cyber notary. The preparation of the parties’ deeds which was previously carried out conventionally has shifted to using online methods as well, thus raising a question about the validity of the identities of the presenters who appear online before the Notary in the process of making authentic deeds in cyber notary. There is a need for synchronous arrangements regarding the conditions for making authentic deeds of the parties which are carried out online. This research is legal research nature perspective, using a statue approach and conceptual approach.